Measurement of Pterygium Tissue Dry Weight Using Two Different Tissue Preparation Techniques in Freeze-Dry Method - Hilmi, Mohd Radzi; Mohd Kamal, Khairidzan; Che Azemin, Mohd Zulfaezal; Esmady Ariffin, Azrin (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2022)
Due to pterygium tissue compression on the corneal surface, it has been hypothesised that the degree of corneal astigmatism caused by pterygium can vary. This study aims to develop a freeze-dried method for estimating net pterygium tissue mass (NPTM) as dry weight. A single surgeon (KMK) excised 60 primary pterygium using the controlled partial avulsion technique and divided them into two groups: formalin-fixed (n=30) and unfixed (n=30). After determining the weight of each sterile container, 5 mL of 5% buffered formaldehyde was added to the formalin-fixed group and stored for one week, while 5 mL of distilled water was added to the non-fixed pterygium group. Each container was pre-frozen for 12 hours before being freeze-dried (-24 hours at -80 degrees Celsius). The result is referred to as the net pterygium tissue mass (NPTM). Using an independent T-test, a comparison of wet and dry weight and percentage of NPTM was conducted between groups. Wet weights for formalin-fixed and non-fixed pterygium were 253.33 82.17 g and 255.17 63.52 g, respectively, while dry weights were 184.92 84.31 g and 179.54 72.85 g. Formalin-fixed pterygium tissue revealed a slightly higher percentage of NPTM than non-fixed pterygium tissue (69.39 13.29% vs. 67.75 13.29%, p = 0.792), but this difference was not statistically significant. The freeze-dried method can be utilised to quantify the NPTM of pterygium fibrovascular tissue and investigate the influence of pterygium translucency on predicting induced-corneal astigmatism.